2021
DOI: 10.1111/jpm.12738
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Experiences of Care at Crisis Resolution Home Treatment Teams: A case study research

Abstract: What is known on the subject?• There are many international studies on CRHTTs; however, there has been little research on nurses' experiences of working with CRHTTs.• Earlier studies focused on the nurses' gatekeeping role but did not explore nurses' perception of care as a construct. What does the paper add to existing knowledge?• This study provides information based on mental health nurses' experiences. It explains the home environment, the therapeutic relationship and the process of mental health nursing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…As shown in Table 1 , most of the articles are research articles ( n = 13), followed by articles dedicated to interventions ( n = 7). In terms of the objectives of the studies included, seven investigate the variables that may affect the dispensing of care ( n = 7) [ 25 , 28 , 30 , 33 , 35 , 38 , 39 ], seven are focused on researching or increasing the training and knowledge of professional caregivers ( n = 7) [ 24 , 29 , 31 , 32 , 36 , 41 ], three are dedicated to researching the working atmosphere and how it can affect care quality ( n = 3) [ 26 , 27 , 40 ], and three investigate the caregiver perspective ( n = 3) [ 22 , 23 , 37 ]. The studies can be divided into quantitative ( n = 14), qualitative ( n = 4) and mixed methods ( n = 2) studies, as well as into cross-sectional ( n = 7), longitudinal ( n = 7), inductive ( n = 3), exploratory ( n = 1), study case (n = 1) and other ( n = 1) studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 , most of the articles are research articles ( n = 13), followed by articles dedicated to interventions ( n = 7). In terms of the objectives of the studies included, seven investigate the variables that may affect the dispensing of care ( n = 7) [ 25 , 28 , 30 , 33 , 35 , 38 , 39 ], seven are focused on researching or increasing the training and knowledge of professional caregivers ( n = 7) [ 24 , 29 , 31 , 32 , 36 , 41 ], three are dedicated to researching the working atmosphere and how it can affect care quality ( n = 3) [ 26 , 27 , 40 ], and three investigate the caregiver perspective ( n = 3) [ 22 , 23 , 37 ]. The studies can be divided into quantitative ( n = 14), qualitative ( n = 4) and mixed methods ( n = 2) studies, as well as into cross-sectional ( n = 7), longitudinal ( n = 7), inductive ( n = 3), exploratory ( n = 1), study case (n = 1) and other ( n = 1) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect that plays a key role in this regard is the proximity provided by home care. This type of care is seen by professional caregivers as an opportunity to get to know the person beyond their role as a patient, which increased their involvement in the job and provided greater satisfaction than conventional care in hospitals or centers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…studies were reviewed based on their title and abstract using the inclusion criteria, leaving 468 remaining studies for full text analysis. With the remaining 3 [11,55,56] studies citation tracking was performed using Google Scholar resulting in an additional 273 hits. After another fulltext analysis 5 [34,[57][58][59][60] additional studies were identified.…”
Section: Plos Onementioning
confidence: 99%
“…The included studies describe outpatient crisis interventions in different settings. Four studies [55,57,58,60] focus on crisis resolution teams (CRTs), also known as crisis resolution home treatment teams (CRHTTs), one study [11] focuses on a crisis assessment and treatment service (CAT), another study [34] was conducted at a metropolitan community mental health service center, and one study [59] focuses on a counseling service. One study [56] researched the professional relationship in brief therapy.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation